Estilo gerencial e capacidade organizacional para mudança: um estudo de caso em uma empresa do setor de implementos rodoviários - Vargas, Katiuscia de Fátima Schiemer (2013)
This study aims to identify the relationship between management styles and the factors that facilitate or hinder organizational changes. Therefore, has been carried out a descriptive and quantitative character survey, through a case study on a company of road implement sector. As a theoretical and data collection basis had been used two instruments with already validated scales: (i) Assessment Scale of Managerial Style (EAEG) - (Melo, 2004), and (ii) Instrument of Organizational Capacity for Change (Neiva, 2004). It was obtained the participation of 307 (three hundred and seven) employees of the company under study. The data were analyzed using descriptive statistics and correlations. Regarding the management style of managers, has been analyzed the styles oriented to the task, the relationship and the situational style, and it was found that, as perceived by the employees, most exercise a task oriented management. When investigating the organizational capacity to change, it was found that, in general, the company has low capacity to change. In turn, the analysis of the standardized mean of the factors that facilitate or hinder transactional change revealed that the organization under study presents levels classified as low for all constructs that comprise these factors, highlighting Bureaucracy and Organizational Continuity and Autonomy of Units and People as factors of high and low level, respectively. Analyzing the average of the factors that facilitate or hinder transformational change, stands out the most significant average, of Turbulence in External Environment, and the very low average of Supportive Coalitions of Change. The investigation of the relationships between management styles and factors that facilitate or hinder organizational change showed that all correlations were significant, positive and moderate, where: among all the management styles investigated and the factors that facilitate change transactional, the associations were of greater intensity with the construct Direction, Flexibility and Reliability in Performance Management; and, among all the management styles and factors that facilitate or hinder transformational change, the associations were of greater intensity with the construct Information Flow. The results allow to infer that the management styles relate to the same constructs of the factors that make up the organizational capacity for change. In other words, regardless of the focus of the manager be oriented to the tasks and results, interpersonal relationships or suitable to the context situation, the influence on the capacity to change is the same.